Evaluación de la operación del sistema eléctrico ecuatoriano con integración de energías renovables no convencionales utilizando herramientas Open Source. - Vásquez Barba, Dennis Bayardo (2023)
In this research project, the economic office of the National Interconnected System was developed with the objective of evaluating its operation, this was carried out through the use of an Open Source computational tool called PowNet, designed to determine the commitment of units that minimizes the operational costs and allow the incorporation of non-conventional renewable energy sources into the Ecuadorian electrical system.To evaluate the operation, a reduced model of the Ecuadorian electrical system composed of 51 bars was developed using the DigSILENT Power Factory software. The simulation of the operation of the electrical system was carried out using a planning horizon for the entire year, which included 8760 hours. Data provided by the National Electricity Operator (CENACH) was combined with data generated from its own approximation techniques, which allowed defining the parameters of the opimur ACIÓN model used by Pownet. Using the Gurobi solver, results were obtained for two scenarios: hydrothermal dispatch and dispatch with the introduction of variable renewable sources.Finally, a comparison was made between the deployment carried out by Pownet and CENACE to validate the solutions obtained and conclude that the proposal developed in this work is a valid alternative to evaluate the Ecuadorian electrical system.